Evaluation of diagnostic and therapeutic procedures in patients with acute pancreatitis - Potyrała, Piotr; Tomczak, Wojciech; Kazzi, Marcel; Winkler-Lach, Weronika; Dorochowicz, Mateusz; Pula, Michal (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Acute pancreatitis remains a clinically significant problem worldwide and in Poland, where its incidence is observed to be twice as high as in the global population. The aim of this study is to describe the latest available guidelines for managing patients diagnosed with acute pancreatitis, including diagnostic methods, radiological approaches, as well as conservative and invasive therapeutic treatment. Materials and Methods: The literature available on PubMed, Scopus, Google Scholar databases, and guidelines from the Polish Society of Gastroenterology was reviewed using the words: „acute pancreatitis”, „pancreas", "AP treatment", and „acute pancreatitis management”. Description of the state of knowledge: Patients with suspicion of acute pancreatitis are mainly diagnosed based on their symptoms using the Revised Atlanta Classification comprising of clinical symptoms, elevated pancreatic enzymes level, and imaging test results. The recommended therapeutic management for patients with acute pancreatitis underlines the importance of conservative treatment before the implementation of invasive procedures, the choice of which should be based on the severity and form of the condition. Summary: The existing recommendations regarding the diagnostic approach in acute pancreatitis emphasize the importance of correlating symptoms with radiological findings obtained through ultrasound, which is a quick and widely accessible diagnostic tool. In therapeutic management, conservative treatment remains significant with the early implementation of nutritional support, along with the appropriate method and timing of surgical intervention depending on the form of acute pancreatitis and the presence of infection.